2020
DOI: 10.1007/s00259-020-04695-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival in patients with IDH-wildtype astrocytic gliomas using dynamic O-(2-[18F]-fluoroethyl)-l-tyrosine PET

Abstract: Purpose Integrated histomolecular diagnostics of gliomas according to the World Health Organization (WHO) classification of 2016 has refined diagnostic accuracy and prediction of prognosis. This study aimed at exploring the prognostic value of dynamic O-(2-[ 18 F]fluoroethyl)-L-tyrosine (FET) PET in newly diagnosed, histomolecularly classified astrocytic gliomas of WHO grades III or IV. Methods Before initiation of treatment, dynamic FET PET imaging was performed in patients with newly diagnosed glioblastoma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…Unlike in our study, in these two studies, gliomas were characterized only by histology according to the WHO classi cation 2007 [1]. In another study by our group [15], the potential of dynamic FET PET parameters, particularly TTP, to identify patients with a prolonged survival before initiation of chemoradiation was already observed, which is also compatible with the present data. Furthermore, the patients included in our study represent a more homogenous group of only partially resected or biopsied IDH-wildtype astrocytic gliomas with a subtle MRI contrast enhancement at the most.…”
Section: Discussionsupporting
confidence: 90%
“…Unlike in our study, in these two studies, gliomas were characterized only by histology according to the WHO classi cation 2007 [1]. In another study by our group [15], the potential of dynamic FET PET parameters, particularly TTP, to identify patients with a prolonged survival before initiation of chemoradiation was already observed, which is also compatible with the present data. Furthermore, the patients included in our study represent a more homogenous group of only partially resected or biopsied IDH-wildtype astrocytic gliomas with a subtle MRI contrast enhancement at the most.…”
Section: Discussionsupporting
confidence: 90%
“…Particularly, as dynamic 18 F-FET PET was previously reported to show a high prognostic value in gliomas in addition to the clinically most important molecular genetic biomarkers according to the 2016 WHO classification [IDHmutation and 1p/19q-codeletion status (14,26)], it would be interesting to evaluate whether the additional prognostic value of PET remains even after further subgroup stratification according to the TERTp mutation status. In order to test this hypothesis, further studies with a larger number of patients (particularly in the relatively small TERTp-wildtype subgroup) are needed to perform multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…As recommended by the Response assessment in Neurooncology (RANO) working group in their clinical guidelines (7)(8)(9), molecular imaging using positron-emissiontomography (PET) with radiolabeled amino acids such as O-(2-18 F-fluoroethyl)-L-tyrosine ( 18 F-FET) is increasingly used for the comprehensive evaluation and characterization of brain neoplasms beyond morphological standard imaging with MRI, e. g. for treatment planning (10)(11)(12)(13), but also for noninvasive tumor characterization at initial diagnosis (14)(15)(16)(17)(18)(19)(20). Recent studies indicated that the IDH-mutational status is highly associated with 18 F-FET PET uptake in brain tumors, especially with the 'minimal time to peak' (TTP min ) on dynamic 18 F-FET PET, and has thus a high diagnostic power for the identification of IDH-wildtype gliomas (21).…”
Section: Introductionmentioning
confidence: 99%
“…Here, PET-guided biopsy has been recommended to improve the diagnostic yield and to avoid the biopsy of inconclusive tissue samples. Indeed, dynamic 18 F-FET PET has been shown to detect aggressive tumor sub-volumes, and dynamic 18 F-FET uptake parameters calculated from time–activity curves have shown to be an independent biomarker for clinical outcome [ 20 , 21 , 22 ].…”
Section: Pet Imaging In the Management Of Patients With Glioma: Past And Futurementioning
confidence: 99%